(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Objectives. To evaluate the anterior segment parameters and densitometric values of cornea and lens in children with anisohipermetropic amblyopia by corneal topography and optical biometry devices. Design. Prospective cross sectional study. Participants. Ambliopic and fellow eyes of 42 children with anisohipermetropic amblyopia (19 males, 23 females, mean age 9.98±3.88 years) and right eyes of 44 healty children from pediatric outpatient (22 males, 22 females, mean age 9.41±4.1 years) were included in this study. Methods. All patients were evaluated with sirius topography and optical biometry. Visual acuities, spherical refractive values, mean keratometric values, axial lengths, central corneal thickness, corneal volume, anterior chamber depth, anterior chamber volume, iridocorneal angle, pupil diameter, white to white, cornea densitometry and lens densitometry of amblyopic eyes, fellow eyes and healthy eyes were compared. Results. Visual acuity was 0.332±0.024, 0.0132±0.0058, 0.001 (LogMAR) for amblyopic, fellow and healthy eyes respectively (p = 0.003), spherical refractive 3.79±2.52, 1.33±1.29 and 0.98±0.39 respectively (p = 0.025). ICA and central corneal densitometry were found lower in amblyopic eyes than in fellow and healty eyes among sirius corneal topography parameters (p value 0.041, 0.001). There was no significant difference between groups in terms of optical biometry parameters except axial length. Conclusion. In our study, we found that there were significant differences in iridocorneal angle, central corneal densitometry between groups. We think that it may be an important parameter in corneal density except for spherical equivalent and axial length in the etiology of hyperopic anisometropic amblyopia.